1999
DOI: 10.1016/s0741-5214(99)70317-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of radial elastic properties in the development of aortic dissections

Abstract: Although the aorta normally functions under radial compressive stresses associated with lumen blood pressure, these results show that the aorta tears radially at a much lower value of stress than would have been predicted from previous studies that have reported longitudinal and circumferential Young's modulus. This could explain why dissections propagate readily once the initial tear occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 16 publications
5
52
0
Order By: Relevance
“…Elastin fibers were generated such that orientation was approximately isotropic within the plane. The radial properties of the aorta are less well established [52,53] but are extremely important because failure of the interlamellar connections dictates delamination and thus aortic dissection. Within the model network, the interlamellar connections were designed to encompass the combined effect of all structural components (smooth muscle cells, fine collagen fibers, and fine elastin fibers) contributing to radial strength.…”
Section: Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Elastin fibers were generated such that orientation was approximately isotropic within the plane. The radial properties of the aorta are less well established [52,53] but are extremely important because failure of the interlamellar connections dictates delamination and thus aortic dissection. Within the model network, the interlamellar connections were designed to encompass the combined effect of all structural components (smooth muscle cells, fine collagen fibers, and fine elastin fibers) contributing to radial strength.…”
Section: Equationmentioning
confidence: 99%
“…While clearly the interlamellar connections encompass some collagen, and the elastic lamina contains large amounts of elastin, we utilized this 1:1 ratio. Initial estimates of the fiber parameters (fiber stiffness, nonlinearity, and failure stretch) for collagen and elastin were based on our previous works [21,43], and those for the interlamellar connections were specified based on MacLean's experimental stress-strain behavior of the upper thoracic aorta subjected to radial failure [53]. Properties were subsequently adjusted such that a single set of model parameters matched results from the suite of experiments performed herein; the final parameter values are given in Table 2.…”
Section: Equationmentioning
confidence: 99%
“…Wall stress is an important factor in aortic dissection, which has been recently addressed by several authors [3,4,26,27,28]. The variations of circumferential, longitudinal, and radial stress along arch at steady flow condition and at systolic acceleration (t 1 ), peak entrance flow (t 2 ) of pulsatile flow have a similar pattern.…”
Section: Discussionmentioning
confidence: 97%
“…Under normal conditions, radial stresses are compressive. MacLean et al [4] showed that the aorta tore radially at a much lower value of radial tensile stress and mentioned that once a false lumen is formed by a dissection, radial tensile forces must exist in the aortic wall. In the present study, radial tensile stress exists due to the structure of arch and deformations of the wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation